1995
DOI: 10.1017/s1352465800015873
|View full text |Cite
|
Sign up to set email alerts
|

Intrusive Thoughts and Auditory Hallucinations: A Cognitive Approach

Abstract: In this paper, an account of auditory hallucinations is outlined, incorporating the phenomena of intrusive thoughts; this is done with reference to the prevailing cognitive models of auditory hallucinations. The account proposes that metacognitive beliefs inconsistent with intrusive thoughts lead to their external attribution as auditory hallucinations, and that such a misattribution is maintained by reducing cognitive dissonance. It is also suggested that the appraisal of the resulting hallucinatory experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
159
3
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(184 citation statements)
references
References 47 publications
18
159
3
4
Order By: Relevance
“…These findings from analogue studies are consistent with data from studies that have employed clinical samples, where patients who experience AH report more frequent intrusive thoughts than do patients who do not experience AH (e.g., Lobban et al, 2002;Morrison & Baker, 2000). Together, these studies provide support for the idea that intrusive thoughts may be the raw material of AH, as suggested by Morrison et al (1995).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…These findings from analogue studies are consistent with data from studies that have employed clinical samples, where patients who experience AH report more frequent intrusive thoughts than do patients who do not experience AH (e.g., Lobban et al, 2002;Morrison & Baker, 2000). Together, these studies provide support for the idea that intrusive thoughts may be the raw material of AH, as suggested by Morrison et al (1995).…”
supporting
confidence: 84%
“…It has been suggested that intrusive thoughts may be the mental events that are misattributed to become AH (Morrison, Haddock, & Tarrier, 1995). In part, this is because both intrusive thoughts and AH have been described as being unwanted, uncontrollable, and distressing (Rachman, 1978(Rachman, , 1981Nayani & David, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have provided evidence for an externalising bias in both clinical and non-clinical subjects (e.g., Baker & Morrison, 1998;Bentall, Baker, & Havers, 1991;Bentall & Slade, 1985a;Brébion et al, 2000;Ensum & Morrison, 2003;Johns & McGuire, 1999;Larøi, Van der Linden, & Marczewski, 2004a;Morrison & Haddock, 1997;Rankin & O'Carroll, 1995;Seal, Crowe, & Cheung, 1997). Furthermore, this stance is in accordance with the general supposition made by several cognitive theorists that hallucinations are inner events misattributed to an external source (e.g., Beck & Rector, 2003;Frith, 1992;Hoffman, 1986;Morrison, Haddock, & Tarrier, 1995). The principle differences between these theories lie in explaining how this externalisation arises.…”
Section: Theoretical Implicationssupporting
confidence: 60%
“…The tendency to interpret and assign meaning to thoughts that intrude on consciousness has been linked to psychological distress, autonomic arousal, auditory hallucinations among the mentally ill, and the propensity to self-harm among people with obsessive-compulsive tendencies (Magee & Teachman, 2007;Morrison, 1994;Morrison, Haddock, & Tarrier, 1995;Najmi et al, 2007).…”
Section: Which Spontaneous Thoughts Are Meaningful and When?mentioning
confidence: 99%